The Babbington case; Or, Nick Carter's strange quest - Carter, Nicholas (House name) (Salt Lake City, UT : Project Gutenberg, 2022)
"The Babbington Case; Or, Nick Carter's Strange Quest" by Nicholas Carter is a detective novel likely written in the early 20th century. The story follows the renowned detective Nick Carter as he investigates a mysterious case involving the death of Edythe Lynne, the daughter of a wealthy man, under suspicious circumstances that suggest murder rather than suicide. The opening of the narrative introduces Nick Carter, who comes across tracks in the snow leading to a lavish estate known as Pleasantglades. Upon further investigation, he uncovers that a man had entered with a woman but only the man emerged, creating questions about the woman's fate. Following his instincts, Carter enters the property and discovers Edythe's lifeless body, apparently a victim of foul play disguised as a suicide. As Carter delves deeper, various connections and questions arise regarding her family and acquaintances, creating an intricate web of motives surrounding her tragic end. The stage is set for a gripping tale of deception, intrigue, and the quest for truth. (This is an automatically generated summary.)
Release date is 2022-10-30
David Edwards, Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Detective and mystery stories; Dime novels